ANALISIS KANDUNGAN LOGAM BERAT KADMIUM (CD) PADA PETANI DI DESA KEDUNGREJO KECAMATAN MEGALUH JOMBANG BERDASARKAN MASA KERJA - Hanum, Galuh Ratmana; Yoessie Wahyudhi, Salza Dilla; Mauliana, Metatia Intan (Jurnal Insan Cendekia, 2024)
Introduction: Agriculture is the main source of livelihood for the people in Kedungrejo Village. Cadmium (Cd) are metals that have a high level of toxicity even in small concentrations. The research site is in the rice fields of Kedungrejo Village, Megaluh District, Jombang Regency with a research time of 2 month. Method :The type of research used is experimental test. The number of samples used is 15 farmers. Objective: The purpose of study was to determine the levels of cadmium (Cd) and the relationship between cadmium in urine and the working period of farmers. This study used the Atomic Absorption Spectrophotometer (AAS) method. Results: The results of this study indicate that the levels of cadmium (Cd) in the urine of farmers are still below the threshold. The correlations test used is the Spearman correlation, the coefficient value between cadmium metal (Cd) and working period is 0.884 with a sig value. 0.000, Conclusion: so that it can be stated that there is a very strong relationship between cadmium (Cd) heavy metals in farmers urine based on working period.